Effects of consecutive days of exercise and recovery on muscle mechanical function - Stewart, R. D.; Duhamel, T. A.; Rich, S.; Tupling, A. R.; Green, H. J. (Medicine & Science in Sports & Exercise, 2008)
Purpose: To investigate the effects of three consecutive days of prolonged exercise on muscle mechanical function, 12 volunteers (V[spacing dot above]O2peak = 44.8 +/- 2.0 mL/kgmin, mean +/- SE) cycled at approximately 60% VO2peak until fatigue.